Individual labor market effects of local public expenditures on sports - Tim Pawlowski; Carina Steckenleiter; Tim Wallrafen; Michael Lechner (Deutsches Institut für Wirtschaftsforschung (DIW), 2019)
By merging administrative data on public finances of all municipalities in Germany with individual data from the German Socio-Economic Panel, we explore whether local public expenditures on sports facilities influences individual labor market outcomes. Our identification strategy follows a selection-on-observables approach and exploits the panel structure of the data covering 12 years between 2001 and 2012. The results of our matching estimations suggest that both women and men living in municipalities with high expenditure levels benefit, exhibiting approximately 7 percent of additional household net income on average. However, this income effect is fully captured by earning gains for men rather than women living in the household. Additional analysis suggests, that these gender differences, which can also be observed in terms of working time, hourly wage and employment status, appear plausible since women in the age cohort under consideration are less likely than men to engage in sports in general and in any of the publicly funded sports facilities in particular. Moreover, improved well-being and health are possible mechanisms that determine how the positive labor market effects for men may unfold.
Keywords: Z20; H72; H75; J31; 330; labor market effects; public expenditures; sports; health; well-being